1961
DOI: 10.1126/science.133.3465.1689
|View full text |Cite
|
Sign up to set email alerts
|

Sounds Emitted by the Bottlenose Dolphin

Abstract: The sonic emissions of the bottlenose dolphin are remarkably complex. Three classes of these sounds are discussed and presented graphically. The sine-type wave whistles range in frequency from about 4000 to 18,000 cycles per second. The clicks contain components of this same frequency range plus some components of higher frequencies. Complex waves of high amplitude and of many frequencies are also emitted in water or in air. Situations in which sounds of one or more of these classes can be elicited simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1963
1963
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 6 publications
2
22
0
Order By: Relevance
“…Simultaneous emission of clicks and tonal calls has been described in bottlenose dolphins [67]; however reports of two-voice whistle production are lacking. If the sound production mechanism for whistles and clicks is similar [68], [69], and if both sets of phonic lips can produce both classes of call [70], then two-voice whistle production may be possible and could explain the structure of signature whistle type SW12.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous emission of clicks and tonal calls has been described in bottlenose dolphins [67]; however reports of two-voice whistle production are lacking. If the sound production mechanism for whistles and clicks is similar [68], [69], and if both sets of phonic lips can produce both classes of call [70], then two-voice whistle production may be possible and could explain the structure of signature whistle type SW12.…”
Section: Discussionmentioning
confidence: 99%
“…The cuts will therefore have to be sorted by hand to pick out the ones with whistles. In addition, some whistles may overlap broadband sounds, particularly since dolphins can produce whistles and broadband sounds simultaneously (Lilly & Miller 1961). Without an extremely advanced filter, this method will miss those sounds.…”
Section: Sturtivant and Datta 1995) What Makes Whistles Different Frommentioning
confidence: 99%
“…However, some whistles were so closely followed or preceded by broad-band sounds that the two sounds were not separated by the extraction program. In fact, a single dolphin can produce whistles and broadband sounds simultaneously (Lilly & Miller 1961). Therefore, whistles were often found overlapping broadband sounds.…”
Section: Automatic Sorting Of Soundsmentioning
confidence: 99%
“…Could the timing of the VS be consistent with an emotional response following dopamine release, as suggested previously (Ridgway et al, 2014)? Lilly and Miller (1961) showed that a solitary dolphin in the laboratory could simultaneously emit pulsed sounds and whistles. Previously, no context has been provided for simultaneous whistling and clicking.…”
Section: Introductionmentioning
confidence: 99%